The Night is Yours - Zachariah, Abdul-Razak; Bobo, Keturah A. (New York : Dial Books for Young Readers, 2019)
From a vantage point high in their apartment, a parent narrates as Amani plays hide-and-seek at night with her friends in the neighborhood.
Keywords: Hide-and-seek -- Juvenile fiction; Night -- Juvenile fiction; Neighborhoods -- Juvenile fiction; Parent and child -- Juvenile fiction; Hide-and-seek -- Fiction; Night -- Fiction; Neighborhoods -- Fiction; Parent and child -- Fiction; Picture books